Simultaneous Observations of EMIC‐Induced Drifting Electron Holes (EDEHs) in the Earth's Radiation Belt by the Arase Satellite, Van Allen Probes, and THEMIS. Issue 5 (2nd March 2022) - Nakamura, S.; Miyoshi, Y.; Shiokawa, K.; Omura, Y.; Mitani, T.; Takashima, T.; Higashio, N.; Shinohara, I.; Hori, T.; Imajo, S.; Matsuoka, A.; Tsuchiya, F.; et al.
Abstract: We present an observation of rapid flux depressions in relativistic electrons, which is referred to as "EMIC‐induced drifting electron holes (EDEHs)." The Arase, Van Allen Probes, and THEMIS detected simultaneously electron flux fluctuations. The time variation of flux shows depressions of 1‐min scale with energy dispersion, which appear only in the relativistic energy range and small pitch angles. These characteristics of the flux depression indicate that electromagnetic ion cyclotron waves caused pitch angle scattering on a short time scale in a longitudinally limited region. The Arase satellite detected the local depression of the phase space density of 1, 000 MeV/G electron, indicating that EMIC waves cause the true loss of electrons. Tracing the energy dispersion profile of EDEHs, we show that EDEHs are formed at localized region in the dusk side. Multisatellite observations demonstrate that a series of EDEHs eventually cause a substantial depression of the radiation belt on 1‐hr time scale. Plain Language Summary: This study focuses on the electrons with energies ranging from hundreds of keV to several MeV in the Earth's radiation belt. This study reports the observation of "EMIC‐induced drifting electron holes (EDEHs)" in electron flux near‐simultaneously detected by four satellites: Arase, Van Allen Probes A and B, and THEMIS‐A. EDEHs were caused by localized electron precipitation induced by structured electromagnetic ion cyclotron waves. The observation of EDEHs clearly shows the energy range of the loss process, the magnitude of the loss, and the longitudinal range. Our results highlight that the detection of EDEHs provides a way of monitoring the macroscopic dynamics of the magnetosphere through particle acceleration, loss, and transport. Key Points: "EMIC‐induced drifting electron hole (EDEH)" was simultaneously detected by four satellites in the radiation belt The radial profiles of phase space density indicate the local losses of relativistic electrons caused by EMIC waves Multisatellite observations reveal that the flux at L * = 5.2–5.4 gradually decreases in a few tens of minutes